2018
DOI: 10.1111/gfs.12388
|View full text |Cite
|
Sign up to set email alerts
|

Forage sorghum quantity and quality as affected by biological phosphorous fertilization

Abstract: To investigate the effects of seed inoculation with phosphate affecting microorganisms on the quantitative and qualitative traits of two forage sorghum (Sorghum bicolor (L.)), genotypes were investigated during 2011 and 2012 field experiments. The experimental treatments consisted of chemical (triple super phosphate (TP)), and biological P fertilizers [mycorrhizal fungus (Rhizophagus intraradices) (AM) + Pseudomonas fluorescens strain 93 (PB)] as well as sorghum genotypes (Speedfed and Jumbo) factorially arran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
1
5
0
2
Order By: Relevance
“…In general, plant growth-promoting bacteria (PGPB) are more efficient under conditions of limited nutrient supply and depend on the interaction with other soil microorganisms and plant genotype (Ehteshami et al, 2018). These bacteria must colonize the roots and remain in the rhizosphere or in the interior of the plants in sufficient numbers to produce the beneficial effects (Ehteshami et al, 2018). In Brazil, sorghum has been cultivated as second crop after maize or soybean and they are frequently sharing the same soil.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, plant growth-promoting bacteria (PGPB) are more efficient under conditions of limited nutrient supply and depend on the interaction with other soil microorganisms and plant genotype (Ehteshami et al, 2018). These bacteria must colonize the roots and remain in the rhizosphere or in the interior of the plants in sufficient numbers to produce the beneficial effects (Ehteshami et al, 2018). In Brazil, sorghum has been cultivated as second crop after maize or soybean and they are frequently sharing the same soil.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one option would be the partial substitution of the soluble fertilizers by the combined use with RP and the inoculation of the plants with PSB, which would increase the availability of this nutrient, reducing the costs of production. Ehteshami et al (2018) indicate the use of soluble chemical fertilizers in some plant growth stages with high nutrient demand, such as seedling and flowering. Thus, synthetic fertilization could be combined with the use of microbial inoculants (biological fertilization), since the microorganisms may not be able to supply all the P demanded by the plant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides high yield, an alternative to forage maize should have a high metabolisable energy content as forage maize is often used as complement to protein-rich grassland feeds in ruminant feeding. Earlier studies have shown significant effects of variety (Oliver et al 2004;Cattani et al 2015;Ehteshami et al 2018) and harvest date (Black et al 1980;Lyons et al 2019) on nutritive value of sorghum. Furthermore, certain types of sorghum varieties have similar nutritive value as forage maize while others have not (Aydin et al 1999;Oliver et al 2004;Sánchez-Duarte et al 2019).…”
Section: Introductionmentioning
confidence: 99%